1990
DOI: 10.1111/j.1600-079x.1990.tb00709.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Effects on the Cytoskeletal Organization of MDCK and Neuroblastoma N1E‐115 Cells

Abstract: Despite the fact that many physiological and pharmacological actions of melatonin (MEL) have been described, its mechanism of action at the subcellular level remains unclear. It has been suggested that MEL has effects on cellular processes that involve microfilaments and microtubules. In the present study MEL effects on the cytoskeleton were evaluated in MDCK and N1E-115 cells in which the microfilaments have been shown to participate in cell morphology and dome formation (MDCK) and the microtubules in neurite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 32 publications
4
38
0
Order By: Relevance
“…[44][45][46] Hormones like estrogens, cortisol, growth hormone, melatonin, T3 and T4 also participate in neuritogenesis as extrinsic factors as well. [47][48][49][50][51] The extracellular environment influences neuronal differentiation through tenascins, hyaluronan and the adhesion molecules collagen and laminin among others. [52][53][54] Several types of receptors such as Trk interact with the environment of the neuron, inducing cell membrane changes mediated by increases in calcium and other second messenger events 55,56 that result in neurite protrusion.…”
Section: Neurite Formationmentioning
confidence: 99%
“…[44][45][46] Hormones like estrogens, cortisol, growth hormone, melatonin, T3 and T4 also participate in neuritogenesis as extrinsic factors as well. [47][48][49][50][51] The extracellular environment influences neuronal differentiation through tenascins, hyaluronan and the adhesion molecules collagen and laminin among others. [52][53][54] Several types of receptors such as Trk interact with the environment of the neuron, inducing cell membrane changes mediated by increases in calcium and other second messenger events 55,56 that result in neurite protrusion.…”
Section: Neurite Formationmentioning
confidence: 99%
“…Recent work has confirmed that the mt1 receptor signals through two inhibitory G␣ proteins (G i2 and G i3 ) that attenuate adenylyl cyclase activity and one stimulatory G␣ protein (G q/11 ) that increases phospholipase C activity [Brydon et al, 1999]. The possibility exists however, that the signaling actions of melatonin could also be due to receptorindependent processes that directly affect calmodulin [Poffenbarger and Fuller, 1976;Cardinali and Freire, 1975;Benitez-King et al, 1990] as melatonin is a small lipophilic molecule capable of traversing the plasma membrane.…”
Section: Introductionmentioning
confidence: 90%
“…To date, what is known about the effects of melatonin at the level of cellular and cytoskeletal structure is that treatment of MDCK, SK-N-SH, and N1E-115 cells with melatonin results in an increase in the number of cells with neurite processes (N1E-115 or SK-N-SH) or "domes" (MDCK) and in an increase in the number of microtubules within these cells [Benitez-King et al, 1990;Melendez et al, 1996;Cos et al, 1996]. Melatonin has also been shown to increase the levels of polymerized tubulin in N1E-115 cells [Melendez et al, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, calcium and calmodulin are involved in processes conferring stability to DNA in proliferating neoplastic cells [108] and melatonin was seen to act as a Ca 2+ -calmodulin antagonist, either directly by interacting with key target enzymes or indirectly via specific protein kinases [109,110].…”
Section: Oncostatic Mechanism Of Actionmentioning
confidence: 99%